# Prove that<

Let Δ = Applying Elementary Row Transformations

R2 R2 – R1 and R3 R3 – R1

Δ = Taking (y – x) and (z – x) common from R2 and R3 respectively

Δ = (y – x) (z – x) Applying R3 R3 – R2

Δ = (y – x) (z – x) Taking (z – y) common from R3

Δ = (y – x) (z – x) (z – y) Expanding along R3, we have

Δ = (x – y) (y – z) (z – x) [0 – 1 {x × p(y2 + x2 + xy) – 1 × (1 + px3)} + p (x + y + z) {x × (y + x) – 1 × x2}

Δ = (x – y) (y – z) (z – x) (-px3 – pxy2 – px2y + 1 + px3 + px2y + pxy2 + pxyz)

Δ = (x – y) (y – z) (z – x) (1 + pxyz)

Hence, the given result is proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers